PENYULUHAN KESEHATAN MANAJEMEN NYERI : TEKNIK RELAKSASI NAPAS DALAM DI RUANG ANYELIR BAWAH RSUD KABUPATEN TANGERANG - Diah Prameswari; Elsa Febrianti Putri; Febi Ratnasari (Nusantara Hasana Journal, 2023)
Any surgery can cause discomfort and trauma to the patient. One of the most common complaints of clients is pain. The pain caused by surgery is usually very painful for the patient. Pain is a very unpleasant and very individual sensation that cannot be shared with others. Pain can occupy a person's entire mind, changing that person's life. However, pain is a difficult concept for clients to communicate. Pain management is one method used in the health sector to deal with pain experienced by patients. Deep breathing relaxation technique is a form of nursing care to teach clients how to do deep breathing, slow breathing (holding inspiration maximally) and how to exhale slowly. In addition to reducing the intensity of pain. This deep breathing relaxation technique can also create peace of mind and reduce anxiety.